Small proline rich protein 2a in benign and malignant liver disease. Issue 3 (27th January 2014) - Mizuguchi, Yoshiaki; Isse, Kumiko; Specht, Susan; Lunz, John G.; Corbitt, Natasha; Takizawa, Toshihiro; Demetris, Anthony J.
<x xml:space="preserve">Abstract</x> STAT3‐driven expression of small proline rich protein 2a (SPRR2a), which acts as an src homology 3 (SH3) domain ligand, induces biliary epithelial cell (BEC) epithelial‐mesenchymal transition (EMT), which, in turn, promotes wound healing. SPRR2a also quenches free radicals and protects against oxidative stress and DNA damage in nonneoplastic BEC. Sprr2a‐induced EMT also increases local invasiveness of cholangiocarcinomas (CC), but prevents metastases. Understanding SPRR2a regulation of EMT has potential for therapeutic targeting in both benign and malignant liver disease. Molecular mechanisms responsible for SPRR2a‐induced EMT were characterized, in vitro, and then evidence for utilization of these pathways was sought in human intrahepatic CC, in vivo, using multiplex labeling and software‐assisted morphometric analysis. SPRR2a complexes with ZEB1 and CtBP on the microRNA (miR)‐200c/141 promoter resulting in synergic suppression of miR‐200c/141 transcription, which is required for maintenance of the BEC epithelial phenotype. SPRR2a induction promotes dephosphorylation and nuclear translocation of the SH3‐domain containing protein GRB2 and an SH3‐domain ligand in ZEB1 is required for SPRR2a‐induced synergic suppression of miR‐200c/141. Multiplex protein labeling of CC and morphometric analyses showed: 1) up‐regulation of ZEB‐1, and 2) down‐regulation of CK19 in intrahepatic CC compared to nonneoplastic BEC, consistent with previous CC proteomic studies showing EMT during cholangiocarcinogenesis. Conclusion: SPRR2a modulates ZEB‐1 signaling by way of miR‐200c/141‐associated EMT through SH3‐domain networks and contributes to benign and malignant BEC wound‐healing responses. (Hepatology 2014;59:1130–1143)